Discrete Waveform Relaxation Method for Linear Fractional Delay Differential-Algebraic Equations - Hongliang Liu; Yayun Fu; Bailing Li (Discrete Dynamics in Nature and Society)
Fractional order delay differential-algebraic equations have the characteristics of time lag and memory and constraint limit. These yield some difficulties in the theoretical analysis and numerical computation. In this paper, we are devoted to solving them by the waveform relaxation method. The corresponding convergence results are obtained, and some numerical examples show the efficiency of the method.